2014
DOI: 10.1111/bjd.13128
|View full text |Cite
|
Sign up to set email alerts
|

Regulated genes in psoriatic skin during treatment with fumaric acid esters

Abstract: FAE treatment induces glutathione and Nrf2 pathway genes in lesional skin of patients with psoriasis. In responders, FAEs specifically regulate the transcription factors PTTG1, NR3C1, GATA3 and NFκBIZ, which are important in normal cutaneous development, and the T-helper (Th)2 and Th17 pathways, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…This approach is similar to the use of phase I drugmetabolizing enzymes, in which cytochrome P450, which is induced by various xenobiotics through the Ah receptor, can be used as indicator of marine pollution (Cajaraville et al, 2000). Daily oral administration of fumaric acid esters over 12 weeks was associated with the increased expression of NRF2 target genes in the skin of patients with psoriasis (Onderdijk et al, 2014). Similarly, a fivefold increase in the mRNA level of NQO1 has been reported in peripheral blood mononuclear cells obtained from cancer patients that received a daily dose of CDDO-Me for 3 weeks (Hong et al, 2012).…”
Section: Biomarkers As Nuclear Factor (Erythroidderived 2)-like 2mentioning
confidence: 99%
“…This approach is similar to the use of phase I drugmetabolizing enzymes, in which cytochrome P450, which is induced by various xenobiotics through the Ah receptor, can be used as indicator of marine pollution (Cajaraville et al, 2000). Daily oral administration of fumaric acid esters over 12 weeks was associated with the increased expression of NRF2 target genes in the skin of patients with psoriasis (Onderdijk et al, 2014). Similarly, a fivefold increase in the mRNA level of NQO1 has been reported in peripheral blood mononuclear cells obtained from cancer patients that received a daily dose of CDDO-Me for 3 weeks (Hong et al, 2012).…”
Section: Biomarkers As Nuclear Factor (Erythroidderived 2)-like 2mentioning
confidence: 99%
“…However, little is known about the physiologic functions of GPR109A in the skin and the possible mechanisms activated by its binding of MMF. In addition, in vitro and animal studies, as well as clinical data, suggest that MMF upregulates the antioxidative transcription factor Nrf2 (Onderdijk et al, 2014;Promsote et al, 2014). Our group is currently attempting to address these questions.…”
Section: Mmf-induced Effects In Keratinocytesmentioning
confidence: 99%
“…Onderdijk et al [19] showed using microarray hybridization studies that the glutathione pathway was activated only in the FAE-treated patients and not in the etanercept group. This was evidenced by an upregulation of several GSTs and depletion enzymes in both responding and nonresponding patients, including GPX2, MGST1 and GSTmu3.…”
Section: Discussionmentioning
confidence: 99%